Implementasi Metode Pembelajaran Role Playing dalam Mata Pelajaran Akidah Akhlak untuk Membentuk Akhlakul Karimah Peserta Didik Era Milenial - Afaf Wafiqoh Nusaibah; Wahyu Ramadan; Yazida Ichsan; M.Sahrul Qhodi Alam; Imam Safi’i (Universitas Muhammadiyah Jember, 2021)
This study discusses the Implementation of Role Playing Learning Methods in Akidah Akhlak Subjects to develop Akhlakul Karimah for Millennial Era Students; The method used in this research is qualitative. The type of research method is library research, or may be called a type of library research. The data sources are obtained from various related journals regarding this research; in this study discusses how the concept of the Role Playing learning method in learning the moral creed and how the implementation of the Role Playing learning method in learning the moral creed; the results in this study shows the application of the type of library research method or can be referred to as a type of library research in learning aqidah morals to form akhlakul karimah is fairly effective in its implementation, initially moral learning is quite boring but when applied the type of library research method or can be called a type of library study according to the correct step the learning becomes increased, the division becomes effective in its implementation. And it is proven from previous research articles that the Role Playing method is effective and can form akhlakul karimah in a student after learning takes place, this can be obtained after learning takes place because students in this case play the learning material directly so that they can easily understand a learning and can be applied in everyday life for students and this makes educators successful in achieving learning goals.